Conditional Correlations and Volatility Links Among Gold, Oil and Istanbul Stock Exchange Sector Returns - Gencer, Gaye; Kilic, Erdem (International Journal of Economics and Financial Issues, 2013)
The aim of this research is to expand the literature of market return volatility for the Istanbul Stock Exchange (ISE) sector indices by analyzing the conjoint impact of oil and gold returns and their volatilities. We use both aggregated and disaggregated data in our study which differentiates it from the others in scope. The analysis is conducted by a multivariate CCC M-GARCH model in order to get some multidimensional interactions in the return and volatility processes of the selected variables. We consider 28 different portfolio investments consisting equal investments in oil, gold and each sector index by turn. We observe that oil GARCH effects are significant and close to unity in each model, positioning oil prices as a major source of portfolio volatility. Gold GARCH effects follow oil GARCH parameters in magnitude, implying that gold prices also have significant effects on portfolio volatility. We report negative correlation coefficients between gold and three sector indices, namely, holding, main metals and commercial sectors. Keywords: Financial Modeling; Risk Analysis and Management; M-GARCH; Stock Markets; Sector Returns JEL Classifications: C32; G11